Use of Unmanned Aerial Vehicles for Monitoring Pastures and Forages in Agricultural Sciences: A Systematic Review - Santos, Wagner Martins dos; Martins, Lady Daiane Costa de Sousa; Bezerra, Alan Cezar; Souza, Luciana Sandra Bastos de; Jardim, Alexandre Maniçoba da Rosa Ferraz [UNESP]; Silva, Marcos Vinícius da; Souza, Carlos André Alves de; Silva, Thieres George Freire da (MDPI, 2024)
With the growing demand for efficient solutions to face the challenges posed by population growth and climate change, the use of unmanned aerial vehicles (UAVs) emerges as a promising solution for monitoring biophysical and physiological parameters in forage crops due to their ability to collect high-frequency and high-resolution data. This review addresses the main applications of UAVs in monitoring forage crop characteristics, in addition to evaluating advanced data processing techniques, including machine learning, to optimize the efficiency and sustainability of agricultural production systems. In this paper, the Scopus and Web of Science databases were used to identify the applications of UAVs in forage assessment. Based on inclusion and exclusion criteria, the search resulted in 590 articles, of which 463 were filtered for duplicates and 238 were selected after screening. An analysis of the data revealed an annual growth rate of 35.50% in the production of articles, evidencing the growing interest in the theme. In addition to 1086 authors, 93 journals and 4740 citations were reviewed. Finally, our results contribute to the scientific community by consolidating information on the use of UAVs in precision farming, offering a solid basis for future research and practical applications.
Keywords: forage crops; machine learning; pasture management; precision agriculture; remote sensing; UAV monitoring